Casamento tradicional na Guiné-Bissau : uma compreensão da instituição do casamento Fula - Baldé, Fatumata Djarai (2024)
The aim of this research is to present the perspectives of the traditional marriage institution of the Fulani ethnic group of Guinea-Bissau, as one of the most important traditional practices of this people. As one of the most important traditional practices of the Fulani people, when people get married, both the man and the woman are given the status of responsibility. The research is based on understanding how the process of this traditional practice works, through interviews with young people, since marriage has different meanings for people of different age groups. The Fulani’s nomadic people because they are cattle breeders and move around looking for suitable places for their herding activities, so these changes have given rise to subgroups. Therefore, they have managed to maintain their language and their way of performing traditional religious marriage ceremonies.